Evaluation of death indicators and disability of patients attended in a stroke unit - Baptista, Simone Cristina Paixão Dias [UNESP]; Juliani, Carmen Maria Casquel Monti [UNESP]; Olbrich, Sandra Regina Leite Rosa [UNESP]; Braga, Gabriel Pereira; Bazan, Rodrigo [UNESP]; Spiri, Wilza Carla [UNESP] (FapUNIFESP (SciELO), 2018)
Objective: to evaluate result indicators for mortality and degree of disability of discharged patients before and after the establishment of the stroke unit care. Method: this is a quantitative, retrospective and cross-sectional study. It was conducted in a public hospital, which had the stroke unit care established in 2011. A total of 245 medical records of admitted patients were analyzed from January 29, 2011 to January 28, 2012. An amount of 63 patients were analyzed six months before the establishment of the stroke unit and 182 patients in the subsequent six months. The Modified Rankin Scale was used in medical records of hospital discharge. It has seven scores (0 to 6), which measure the functional impairment, ranging from “no symptoms at all” to “dead”. For data analysis, it was used a statistical analysis software (SAS for Windows®, version 9.3). Results: adding the indicators 0 and 1 (“no symptoms at all” and “no significant disability”) of the Modified Rankin Scale, we found 6.72% before and 42.86% after the establishment, indicating lower disability condition in discharge after establishment. Mortality was 20.69% before establishment and 12.73% after. Conclusion: there was a reduction of the patient’s degree of disability and mortality after establishment of the stroke unit.
Evaluación de los indicadores de óbito e incapacidad de los pacientes atendidos en una unidad de accidente vascular cerebral
Avaliação dos indicadores de óbito e incapacidade dos pacientes atendidos em uma unidade de acidente vascular cerebral
Keywords: Health evaluation; Health services administration; Indicators; Nursing; Stroke